2023
DOI: 10.3390/nano13020241
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanically Coupled III-N Quantum Dots

Abstract: We exploit the three-dimensional (3D) character of the strain field created around InGaN islands formed within the multilayer structures spaced by a less than 1-nm-thick GaN layer for the creation of spatially correlated electronically coupled quantum dots (QDs). The laterally inhomogeneous vertical out-diffusion of In atoms during growth interruption is the basic mechanism for the formation of InGaN islands within as-deposited 2D layers. An anisotropic 3D strain field created in the first layer is sufficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, the β-phase and the γ-phase are the most desirable polymorphs as they exhibit strong electrical dipole moments that are responsible for the enhanced piezoelectric activities. 42 Gee and colleagues applied the electrospinning method to produce piezoelectric PVDF nanofiber membranes, and their statistical analysis revealed that the solvent ratio and flow rate are the primary factors affecting the β-phase fraction. 43 Additionally, research by Khalifa and colleagues explored the combined impact of electrospinning and nanofillers, finding that these elements significantly enhance the β-phase fraction.…”
Section: Resultsmentioning
confidence: 99%
“…However, the β-phase and the γ-phase are the most desirable polymorphs as they exhibit strong electrical dipole moments that are responsible for the enhanced piezoelectric activities. 42 Gee and colleagues applied the electrospinning method to produce piezoelectric PVDF nanofiber membranes, and their statistical analysis revealed that the solvent ratio and flow rate are the primary factors affecting the β-phase fraction. 43 Additionally, research by Khalifa and colleagues explored the combined impact of electrospinning and nanofillers, finding that these elements significantly enhance the β-phase fraction.…”
Section: Resultsmentioning
confidence: 99%
“…34 Ungerer et al investigated the electron distribution and magnetic properties of Ru fcc nano-dots, both in icosahedral (13 and 55 atoms) and cubic shape (13 and 63 atoms). 35 Similarly, the Cu 55 nanocluster is also known for its several applications as a catalyst. Among other applications, it is used in acetylene hydrogenation, methanol and ethanol formation from syngas, conversion of CO 2 to hydrocarbon fuels, CO oxidation, and as a degradant agent for SF 6 molecules.…”
Section: Introductionmentioning
confidence: 99%
“…2D materials like Molibdenum or Tungsten Disulphide retains excellent electrical transport even at the monolayer level, and their deep study according to different atmospheric environment [7] is of enormous interest for the future development of digital electronics and of all applications based on it such as artificial intelligence [8]. Regarding 0D nanomaterials the three papers [9][10][11] mainly focused on the very important topic of modelling quantum dots constituted by III-V elements with a special dedication possible electromechanical coupling possibly present in flexible displays electronics like in the Samsung high quality products series Zflip-Zfold.…”
mentioning
confidence: 99%